Associations between neurological examination at term-equivalent age and cerebral hemodynamics and oxygen metabolism in infants born preterm - Côté-Corriveau, Gabriel; Simard, Marie-Noëlle; Beaulieu, Olivia; Chowdhury, Rasheda Arman; Gagnon, Marie-Michèle; Gagnon, Mélanie; Ledjiar, Omar; Bernard, Catherine; Nuyt, Anne Monique; Dehaes, Mathieu; Luu, Thuy Mai (Frontiers in Neuroscience, 2023)
Background Infants born at 29–36 weeks gestational age (GA) are at risk of experiencing neurodevelopmental challenges. We hypothesize that cerebral hemodynamics and oxygen metabolism measured by bedside optical brain monitoring are potential biomarkers of brain development and are associated with neurological examination at term-equivalent age (TEA). Methods Preterm infants (N = 133) born 29–36 weeks GA and admitted in the neonatal intensive care unit were enrolled in this prospective cohort study. Combined frequency-domain near infrared spectroscopy (FDNIRS) and diffuse correlation spectroscopy (DCS) were used from birth to TEA to measure cerebral hemoglobin oxygen saturation and an index of microvascular cerebral blood flow (CBFi) along with peripheral arterial oxygen saturation (SpO2). In combination with hemoglobin concentration in the blood, these parameters were used to derive cerebral oxygen extraction fraction (OEF) and an index of cerebral oxygen metabolism (CMRO2i). The Amiel-Tison and Gosselin Neurological Assessment was performed at TEA. Linear regression models were used to assess the associations between changes in FDNIRS-DCS parameters from birth to TEA and GA at birth. Logistic regression models were used to assess the associations between changes in FDNIRS-DCS parameters from birth to TEA and neurological examination at TEA. Results Steeper increases in CBFi (p < 0.0001) and CMRO2i (p = 0.0003) were associated with higher GA at birth. Changes in OEF, CBFi, and CMRO2i from birth to TEA were not associated with neurological examination at TEA. Conclusion In this population, cerebral FDNIRS-DCS parameters were not associated with neurological examination at TEA. Larger increases in CBFi and CMRO2i from birth to TEA were associated with higher GA. Non-invasive bedside FDNIRS-DCS monitoring provides cerebral hemodynamic and metabolic parameters that may complement neurological examination to assess brain development in preterm infants.